Exploring the Role of the Student Affairs Office in Enhancing the Cultural and Social Experiences of International Students in China (Journal of Student Affairs in Africa, 2021)
Many universities are hosting and enrolling international students as an important aspect of their internationalisation mission of higher education. However, many international students experienced significant problems adjusting into a host culture and social milieu. Informing this qualitative study were 45 international students in a top-tier comprehensive research university in Southeast China. The study focuses on the experience of international students towards the role played by international Fu Da Yuans (Counsellors) in enhancing the students’ cultural and social experiences at the university. The results indicate that the four most significant adjustment issues for international students are the language challenges, social interaction with Chinese students, cultural orientation programmes, and counselling services for international students. Building on the U-Curve adjustment theory (Oberg, 1960), the study revealed the importance of international Fu Da Yuans to provide cultural and social support to international students for easy adjustment into a new culture and social setting. The study bears practical implications to providing international Fu Da Yuans with important insights that can help to create an environment conducive to enhancing the cultural and social experiences of international students.
Keywords: cultural experience; social experiences; Fu Dao Yuan; student affairs office; international students